Laser weld: microstructure and corrosion study of Ag-Pd-Au-Cu alloy of the dental application - Santos, M. L.; Acciari, H. A.; Vercik, LCO; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 2003)
The laser Welding process was introduced into dentistry by the end of the 1980s, resulting on a great impulse to that area with the development of cheaper and smaller equipment, using simpler technique. This allowed greater use of that process on the confection of prostheses compared to the brazing process since the heat source for that process is a concentrated light beam of high power, which minimizes distortion problems on the prosthetic pieces. Ag-Pd-Au-Cu alloy used on the confection of dental implant prostheses was observed before and after subjection to the laser welding process. The microstructure was analyzed with the. use of optic microscopy and the corrosion resistance was studied by the traditional electrochemical techniques and by electrochemical impedance, under environmental conditions simulating the aggressiveness found in the mouth cavity. A structural change was detected on the weld area, which presented a refined microstructure deriving from the high-speed cooling. The base metal out of the weld area presented a fusion coarse microstructure. The electrochemical essays showed differences on the potentiodynamic polarization behavior in both weld and metal base areas, indicating superior corrosion resistance in the weld area. The impedance spectra were characterized by capacitive distorted components, presenting linear impedance in the low frequencies area. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: Ag-Pd-Au-Cu; laser; corrosion; dental alloys